Comparative study of VitAto flour and wheat flour on proximate analysis and the effect of addition of wheat flour to VitAto flour - Mohamad Yusri, Khairulnissah Asilah (2020)
VitAto is one of the variety of Ipomoea species or known as sweet potato. It is one of the crucial staple food that being cultivated in Malaysia. It growth abundantly in this country however in term of its utilization, this sweet potato's variety are still underutilized. Therefore, this study aim to produce a flour from sweet potato variety that is VitAto and compare the nutritional value of this VitAto flour with commercial flour as well as to investigate the effect on physicochemical properties when adding VitAto flour to wheat flour. The proximate analysis was performed to determine the moisture content, ash, protein, crude fat and carbohydrate. This result obtained from this study indicates that VitAto flour contain high in carbohydrate (81.35%) and lower in moisture content (11.57%), ash content (3.17%), crude fat (1.02%) and protein (2.88%) compared to commercial wheat flour whereas 57.37% carbohydrate, 13.31% of moisture, 9.12% ash, 2.82% crude fat and 12.79% protein. The physicochemical properties analysis shows that increasing ratio of VitAto flour in wheat flour, will increase the properties in term of water absorption index and water solubility index while decreasing in fat absorption index. This study found that VitAto flour capable to be an alternative for wheat flour and also can be utilize as multipurpose flour in many food product especially for bakery goods.